Associations of dietary factors with gastric cancer risk: insights from NHANES 2003–2016 and mendelian randomization analyses - Zhang, Yigang; Wang, Sen; Li, Qingya; Liu, Hongda; Xuan, Zhe; Li, Fengyuan; Li, Zheng; Xia, Yiwen; Jiang, Tianlu; Xu, Penghui; Fang, Lang; Wang, Linjun; et al. (Frontiers in Genetics, 2024)
Background: Gastric cancer (GC) continues to be a leading cause of cancer-related deaths globally. Diet significantly influences the incidence and progression of GC. However, the relationships between dietary intakes and GC have shown inconsistency. Methods: This study included adults who participated in the National Health and Nutrition Examination Survey (NHANES) conducted from 2003 to 2016. The investigation aimed at assessing the associations between 32 dietary factors and GC. To further detect potential causal relationships between dietary factors and the risk of GC, a two-sample Mendelian randomization (MR) analysis was conducted. The primary analytical method employed was the Inverse Variance Weighted (IVW) analysis. Additionally, the results from the IVW analysis were further validated by employing four other methods. Results: Of 35,098 participants surveyed, 20 had a history of GC. By conducting weighted logistic multivariate analysis, we observed positive correlations of total fat intake [odds ratio (OR) = 1.09, 95% confidence interval (CI): (1.01,1.17), p=0.03] and negative association of dietary monounsaturated fatty acids (MUFA) intake [OR = 0.83, 95%CI: (0.76,0.92), p<0.001] with GC. In addition, we further evaluated the odds of GC across the quartiles of dietary MUFA and found that the top quartile of total MUFA intake was associated with lower likelihood of GC in three different models [model1: OR = 0.03, 95%CI: (0.00,0.25), p<0.01; model2: OR = 0.04, 95%CI: (0.00,0.38), p=0.01; model3: OR = 0.04, 95%CI: (0.00,0.40), p=0.01]. As for MR analyses, genetic instruments were selected from The IEU Open GWAS project. IVW showed that GC risk was not associated with MUFA [OR = 0. 82, 95%CI: (0.59-1.14), p= 0.23] or ratio of MUFA to total fatty acids [OR = 1.00, 95%CI: (0.75-1.35), p= 0.98]. Similar results were observed when using other MR methods. Conclusions: The NHANES study revealed that consuming MUFA was linked to a reduced risk of GC, although the results from MR analyses did not provide evidence of a causal relationship. Additional research is necessary to clarify our findings.